2023
DOI: 10.1111/jhn.13130
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a dietitian in general practice: paediatric food allergy

Abstract: Background: Food allergy in infants and young children places a significant burden on primary care. This study evaluated a dietetic-led paediatric food allergy service, which attempts to provide more rapid access to the dietitian and reduce the need for general practitioner (GP) and secondary care appointments. Methods: Two community dietetic services for children referred with food allergy were compared. The first was dietetic-led care where dietitians train community children's nurses to recognise potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Pediatricians and allergists are central to the effective multidisciplinary management of food allergies. Furthermore, there may be scope for other members of the multidisciplinary team to play a larger role in patient care ( Figure 2 ) to aid pediatricians and allergists in supporting their patients with food allergy treatment: A large feasibility trial demonstrated the potential of nurse-led allergy clinics in delivering remote and face-to-face consultations with patients to ease the burden on primary care services ( 87 ) Dieticians provide crucial nutritional and dietary support to patients on restrictive diets, as well as education on allergen avoidance, and dietician-led services also have potential to reduce primary and secondary care appointments ( 88 ) Patients with multiple food allergies may benefit most from nutritional counselling ( 37 ) and it is recommended by the NIAID for all food allergy patients ( 6 ) Community pharmacists are able to work collaboratively with pediatricians and allergists to provide ongoing assistance by retraining patients on the use of epinephrine autoinjectors and reviewing the signs of an allergic reaction ( 89 ) Food allergies can lead to significant psychosocial impact and mental health support may be beneficial to reduce anxiety among patients and caregivers ( 90 ) …”
Section: Management Optionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pediatricians and allergists are central to the effective multidisciplinary management of food allergies. Furthermore, there may be scope for other members of the multidisciplinary team to play a larger role in patient care ( Figure 2 ) to aid pediatricians and allergists in supporting their patients with food allergy treatment: A large feasibility trial demonstrated the potential of nurse-led allergy clinics in delivering remote and face-to-face consultations with patients to ease the burden on primary care services ( 87 ) Dieticians provide crucial nutritional and dietary support to patients on restrictive diets, as well as education on allergen avoidance, and dietician-led services also have potential to reduce primary and secondary care appointments ( 88 ) Patients with multiple food allergies may benefit most from nutritional counselling ( 37 ) and it is recommended by the NIAID for all food allergy patients ( 6 ) Community pharmacists are able to work collaboratively with pediatricians and allergists to provide ongoing assistance by retraining patients on the use of epinephrine autoinjectors and reviewing the signs of an allergic reaction ( 89 ) Food allergies can lead to significant psychosocial impact and mental health support may be beneficial to reduce anxiety among patients and caregivers ( 90 ) …”
Section: Management Optionsmentioning
confidence: 99%
“…Dieticians provide crucial nutritional and dietary support to patients on restrictive diets, as well as education on allergen avoidance, and dietician-led services also have potential to reduce primary and secondary care appointments ( 88 )…”
Section: Management Optionsmentioning
confidence: 99%
“…This aim is generally achieved through a traditional method, where patients are predominantly referred by the general practitioner. Collinson et al developed a specific model, providing more rapid access to the dietitian, reducing the need for general practitioner (GP) and secondary care appointments, and reducing the time taken to receive dietetic input, thereby resolving symptoms more quickly [ 52 ]. Success in managing the diet of patients with FA depends on a team combining pediatric allergist and dietitian expertise to educate patients and families on appropriate allergen avoidance and replacement to ensure nutritional needs [ 49 ].…”
Section: Nutritional Aspectsmentioning
confidence: 99%